A case of successful oral commissure and vermilion reconstruction following extensive full-thickness cheek resection of advanced buccal carcinoma. Issue 4 (July 2020) - Kume, Kenichi; Hijioka, Hiroshi; Ishida, Takayuki; Okawachi, Takako; Nishihara, Kazuhide; Sugiura, Tsuyoshi; Nakamura, Norifumi
Abstract: Enabling patient to take and eat food is the most important goal in the oral and maxillofacial surgery, however, there has been no golden standard method for oral commissure and vermilion reconstruction for full-thickness cheek defects. In this report, a technique of oral commissure and vermilion reconstruction using a latissimus dorsi (LD) flap and subsequent vermilion reconstruction with a lateral tongue flap following extensive full-thickness cheek resection of advanced buccal carcinoma is described. A 68-year-old woman with buccal carcinoma progressing to the left cheek skin, oral commissure, and over one-third of the upper and lower vermilion visited our hospital. Following extensive full-thickness resection of cheek and upper and lower lips, reconstruction of extensive defects using an LD musculocutaneous flap was carried out at the first stage. One year after the first operation, oral commissure and vermilion reconstruction was carried out, in which the upper lip was produced using part of the skin of the LD flap and a new lower lip was produced by preparing a pedicle flap form lateral tongue. Oral vestibular expansion was combined by advancing the upper and lower gingival mucoperiosteal tissues to the top and bottom of the intraoral buccal area. Five-year postoperative results showed an esthetically and functionally favorable lower face and symmetrical lips without disturbance of oral food intake.